The Effect of Government Support on Startups in Saudi Arabia - Ghalia Abdulhafiz Dawood, Yosra Hamas (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Entrepreneurship plays a key role in contributing to the country's economy by elevating the country's growth and development. Entrepreneurship is an important factor that facilitates poverty reduction, employment opportunities and economical changes. This work was done to examined the contribution of government policies in Saudi Arabia towards start-ups business. For this work, quantitative method was used. The number of samples for this work was 100 business startup owners and partners in Jeddah. Data collection was done using survey questionnaires and analyzed in terms of basic statistics. The findings of this work have confirmed that the government providing support to start-ups business. The results have shown that 73% of the respondents have received governmental support for their business. Furthermore, the results have shown that 33 % have received funding support, 20 % have received networking support, 10 % have received equipment support, 10 % have received workshop support and 27 % have received other resources support. It is therefore concluded that Saudi Arabia government provides support to start-ups business.